Correlation of Obesity Status with Zinc Serum Levels and Insulin Resistance in Perimenopause Obese Women - Heidi Listya; Muhammad Sulchan; Etisa Adi Murbawani; Niken Puruhita; Amalia Sukmadianti (Faculty of Medicine, Diponegoro University, 2020)
Background : Obesity is one of the global health problems. The prevalence of obesity in women is higher than men. Various metabolic problems are caused by obesity, such as insulin resistance and deficiency of micronutrients such as zinc. The occurrence of insulin resistance in obesity is also influenced by zinc deficiency.Objectives : To analyse the correlation of obesity status with serum zinc levels and insulin resistance in perimenopause obese women.Methods : Correlational research with 62 perimenopause obese women subject aged 40-50 years old who met the inclusion and exclusion criteria. Serum zinc levels were measurement using AAS and insulin resistance using HOMA IR formula. Serum zinc levels, fasting insulin, fasting blood glucose taken from venous blood. Hypothesis testing uses Pearson correlation.Results : 12.9% had low serum zinc levels and high HOMA IR 9.09%. There was a significant negative correlation between BMI with serum zinc levels (r = -0.402; p = 0.001) and significant positive correlation between BMI with insulin resistance (r = 0.396; p = 0.001). There was a significant negative correlation between WC with serum zinc levels (r = -0.18 , p = 0.161) and significant positive correlation between WC with insulin resistance ( r =0.284 , p =0.025 ). and significant negative correlation between serum zinc levels with insulin resistance (r = -0.404; p = 0.001).Conclusion : There is a correlation between obesity status with serum zinc levels and correlation between obesity status with insulin resistance in perimenopause obese women.